Pengaruh Media Augmented Reality Terhadap Hasil Belajar Siswa Materi Sistem Pencernaan Manusia Kelas V SDN 30 Pangkalpinang - Armadi Syahbani; Erika Fitri Wardani; Rifki Hanif Setiawan (JBES (Journal Basic Education Skills), 2026)
The main issue underlying this study is the low learning outcomes of students in the topic of the Human Digestive System. The learning outcomes of students did not meet the minimum competency standard (KTTP) of 70. The researcher intended to analyze the effect of augmented reality media on the learning achievements of fifth-grade students at SD Negeri 30 Pangkalpinang in the topic of the Human Digestive System. The approach used is quantitative with a quasi-experimental design method of the nonequivalent control group design type. In this study, a saturated sampling technique was applied with class VA as the experimental group and class VB as the control group, totaling 55 students. The data collection process was conducted through tests, while data analysis included Kolmogorov-Smirnov normality testing, Levene's homogeneity testing, and hypothesis testing using an independent sample t-test. From the normality and homogeneity tests, it was concluded that the data distribution was normal and both variants were homogeneous. Meanwhile, the hypothesis test results obtained a Sig. value < 0.05, namely 0.030, meaning that Ha was accepted and Ho was rejected. This calculation shows that there is an impact of Augmented Reality on the learning achievement of fifth-grade students on the topic of the Human Digestive System at SD Negeri 30 Pangkalpinang.